Normalization of keratinocyte-type integrins during the establishment of the oral mucosa phenotype in vitro - Tomakidi, Pascal; Breitkreutz, Dirk; Kohl, Annette; Komposch, Gerda (Annals of anatomy, 1999)
In stratified epithelia, integrins play a fundamental role in mediating basal cell attachment to a variety of extracellular matrix molecules. To assess whether keratinocyte-specific integrins are expressed in a similar way as in the normal situation also under in vivo related conditions, we processed oral mucosa equivalents consisting of keratinocytes and fibroblasts from non-cornified gingiva.
Elektronische Reproduktion der Druck-Ausgabe
Available online 16 August 2005
Gesehen am 05.02.2021